Neuron stress-related genes serve as new biomarkers in hypothalamic tissue following high fat diet - Liang, Caixia; Lu, Hongjian; Wang, Xueqin; Su, Jianbin; Qi, Feng; Shang, Yanxing; Li, Yu; Zhang, Dongmei; Duan, Chengwei (Frontiers in Endocrinology, 2024)
Objective: Energy homeostasis is modulated by the hypothalamic is essential for obesity progression, however, the gene expression profiling remains to be fully understood.Methods: GEO datasets were downloaded from the GEO website and analysed by the R packages to obtain the DEGs. And, the WGCNA analysis and PPI networks of co-expressed DEGs were designed using STRING to get key genes. In addition, the single-cell sequencing datasets and GTEx database were utilized to receive the neuron-stress genes from the key genes. Further, high-fat diet (HFD)-induced hypothalamic tissue of mice was